Analysis of Breast Cancer Receptors Status and Molecular Subtypes Among Female Population - Sameena Naz, Mashall Siddiqui, Amir Iqbal Memon, Aisha Masroor Bhatti, Zoiya Inayat Hussain, Iqra, (Pakistan Journal of Medical & Health Sciences, 2023)
One of the leading cause of deaths in women is breast cancer. The incidence and prevalence of cancer is increasing day by day. The aim of this research was to analyse the relationship between HRS (hormonal receptor status) and age in females suffering from breast cancer. It was a cross-sectional study conducted at surgical department, LUMHS, Jamshoro, Sindh, Pakistan. The 200 females diagnosed with breast cancer were included in research. The mean age of the study sample was observed to be 48.68 ± 9.54 years. Out of 200 females, 79 (39.5%) females had positive expression of “ER (estrogen receptor)” while 80, (40%) had positive “PR (progesterone receptor)” expression and 41(20.5%) females were associated with “positive expression of HER2/neu (human epidermal growth factor receptor 2)”. The age group of 41-50 years showed (30.4%) highest ratio of positive ER followed by (24%) PR and (17.5%) “HER/2 neu expression” respectively. A statistically significant correlation was found between ER expression and age and (p=0.013), PR expression and age and (p=0.002) while HER/2 neu expression showed insignificant correlation (p=0.231). The research also found that most of the females in their 40s were suffering from breast cancer also the older women had positive were “estrogen receptor (ER), progesterone receptor (PR), and HER2/neu expression” as compared to younger females but there are high chances of survival if breast cancer is diagnosed and managed timely. To do so awareness regarding self-care and self-analysis for women is important to prevent the prognosis of breast cancer. Keywords: Breast Cancer, hormonal receptor status, estrogen, progesterone